Institutions and the sectoral organization of production - Ana Fernandes (University of Bern, Department of Economics, 2012)
The impact of economic institutions on development is presently taken for granted but there is surprisingly scarce evidence on the channels through which institutions affect the organization of output. Imperfections in contractual enforcement, for example, could lead firms to adopt technologies that inefficiently minimize dependence on other sectors, thus going hand in hand with a reduction in productivity. Another channel would be the concentration of economic activity in sectors that have fewer interactions with other sectors. Using a dataset on manufacturing, this paper presents empirical evidence supporting both effects: better contractual enforcement raises relatively more the labor share of sectors that interact more with other sectors; further, good governance also boosts relatively more labor productivity in more complex subsectors of manufacturing. Both effects are strongest among countries whose labor productivity ranks in the second and third quartiles of the world productivity distribution and they are mute for the two extreme groups of poor and developed economies.
Keywords: O43; P16; 330; sectoral organization of output; institutions; contractual enforcement; input-output; complexity; Institutionelle Infrastruktur; Rechtsdurchsetzung; Technologiewahl; Produktivität; Verarbeitendes Gewerbe; Input-Output; Schweiz